2018
DOI: 10.21278/tof.42207
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Analysis and Theoretical Modelling of Cutting Parameters in the Drilling of AISI H13 Steel with Coated and Uncoated Drills

Abstract: SummaryIn this study, drillability experiments were carried out on the AISI H13 hot work steel which is difficult to machine. Uncoated and AlCrN-coated carbide drills, ø14 mm, were used at 4 cutting speeds (60, 75, 90 and 108 m/min) and three different feed rates (0.15, 0.20 and 0.25 mm/rev). As a result of the experimental work, it was observed that an increase in the feed rate caused an increased on the thrust force in the workpiece machined with both the uncoated and coated drills. While an increase in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 11 publications
1
9
0
Order By: Relevance
“…At the high cutting speed and low feed rate, it was apparent for chips to evacuate along the hole axis due to shortened chip and coated drill contact based on low friction and high wear resistance of the AlCrN coated-WC drill. This result agreed with the previous study found in [15]. Although drilling at higher cutting speeds gave more productivity than drilling at lower cutting speeds, it resulted in accelerated tool wear or failure and higher EBH formation.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…At the high cutting speed and low feed rate, it was apparent for chips to evacuate along the hole axis due to shortened chip and coated drill contact based on low friction and high wear resistance of the AlCrN coated-WC drill. This result agreed with the previous study found in [15]. Although drilling at higher cutting speeds gave more productivity than drilling at lower cutting speeds, it resulted in accelerated tool wear or failure and higher EBH formation.…”
Section: Resultssupporting
confidence: 93%
“…In this work, CNC drilling machine was employed to carry out the experiments under dry condition for making the specific hole of the forging brass workpieces for producing the water-valve components using the uncoated-WC and the AlCrN coated-WC drills. It is noted that AlCrN was considered to be an alternative coating material for drilling tools due to its excellent properties such as low thermal conductivity, better abrasive wear resistance, low friction coefficient, high hardness, elastic modulus, H/E ratio, and bonding condition between coating and the unique carbide substrate [13][14][15]. Tool life models of both drills were developed in terms of cutting speed and feed rate using Taylor's equation with a maximum EBH value of 0.16 mm for the tool life criterion based on manufacturer's specifications and customer's requirement.…”
Section: Introductionmentioning
confidence: 99%
“…This is caused from the higher feed rate that is applied. Finally, bar 3 shows a simulation model that was studied in [12], where the cutting conditions that were used are the same with the ones mentioned in Table 5, the drill has similar characteristics (geometry and coating) with the current work and the workpiece is also H-13 steel. In this bar, the thrust is over 3600 N , and this is probably due to the fact that the tool is slightly larger in diameter ( D =14 mm) in comparison to the current work, where the nominal diameter of the drill is D =10 mm.…”
Section: Cutting Conditions Symbol Valuesmentioning
confidence: 99%
“…Tekaüt et al in [12] evaluated different cutting parameters in drilling of H-13 steel in soft and annealed condition with the use of coated and uncoated carbide twist drills. They concluded that an increase in cutting speed leads to high stresses and higher wear values for the uncoated drills, especially on drills' center, because of their difficulty to evacuate the produced chips.…”
Section: Introductionmentioning
confidence: 99%
“…During the preparation of the samples many problems occur due to the high hardness of the base metal. Although there were even cutting area temperatures reaching up to 600 °C during the processing, hardness did not decrease and the steel maintained high strength [20]. Two specimens and another one as a spare specimen were prepared for each temperature.…”
Section: Properties Of the Tested Material Heat Treatment Of Plates And Preparation Of Samplesmentioning
confidence: 99%